Development of an Instrument Based on Salient Behavioral Beliefs to Measure Attitude towards Physical Education - Moroo Mario; Anindita Das (OVS LLC, 2022)
Study purpose. The study purpose was to develop an instrument to measure students' attitude towards physical education through salient behavioral beliefs. Materials and methods. The participants of the study were both boys and girls of grades 7 to 10 from the state of Manipur (India) in the first, second and fourth phase. In the first phase, based on the recommendation of the theory of reasoned action and its extension, the theory of planned behavior, an elicitation study was conducted using open-ended questions, where a total of 308 student responses were collected. The student responses were used to develop items through content analysis. In the second phase, i.e. content validity study, a total of 5 experts were recruited to evaluate the developed items from the elicitation study. In the third phase i.e. pilot study, out of the total of 123 student responses, 104 student responses were found to be usable for analysis. In the fourth phase, i.e. main study, out of the total of 433 student responses, 377 student responses were found to be usable for analysis. Results. Due to lack of good model fit from the pilot study, a second exploratory factor analysis was conducted with the first half of the main study data which produced a three-factor model, and this model was tested with confirmatory factor analysis with the other half of the main study data. The model fit indices were found to be appropriate, and also the composite reliability and construct validity were found to be appropriate. Conclusions. This belief-based attitude measuring instrument was found to be valid and reliable for grades 7 to 10 in the Indian physical education context, i.e. schools which incorporate both yoga and physical education in the general physical education curriculum.